C-Reactive Protein and Leukocyte as Predictors of Complications in Peripheral Arterial Disease - Yongky Wijaya; Riri Andri Muzasti (Sumatera Medical Journal, 2021)
Peripheral Arterial Disease (PAD) is the narrowing of peripheral blood vessels which prevalence is high in the elders. In 2010, it was estimated that 202 million people were suffering from PAD, most of which are in developing countries, especially the Southeast Asia region. Inflammation markers such as leukocyte and C-Reactive Protein (CRP) can predict the incidence of PAD but their use in determining prognosis remains unclear. Complications in PAD include amputation, increased cardiovascular events, and even death. Aim: This study aims to determine the relationship between leukocyte and CRP level on complications in PAD, in the forms of amputation, cardiovascular events, and mortality. Methods: This is a meta analysis study which uses online literature sourced from Pubmed, Science Direct, Cochrane, and Google Scholar. Results: Based on the data analysis, there is a significant relationship between CRP with the incidence of amputation (HR 1.24, 95%CI: 1.02-1.49, p=0.03) and hs-CRP with cardiovascular events (HR 1.33, 95%CI: 1.10-1.60, p=0.003). Leukocyte on the other hand shows no significant relationship with the incidence of amputation (OR 1.10, 95%CI: 0.98-1.23, p=0.10) and mortality (OR 1.14, 95%CI: 0.97-1.35, p=0.12)